IAS 38 Disclosure Compliance by Czech Listed Companies - Procházka, David (Studia Oeconomica Posnaniensia, 2019)
This paper tests empirically the compliance with IAS 38 disclosure requirements by Czech listed companies. Using a dataset of financial and non-financial firms from the period 2008-2017, we have documented a moderate increase in disclosure quality of the sample firms over the period. Consistently with recent research, the evidence of improvement can be attributed to reporting incentives of the firms, acknowledging the importance of the capital market to raise capital and, thus, to deliver useful information to the users of financial statements. However, the analysis reveals heterogeneity in the level of compliance across the firms, de-\pending on a company's auditor and their ownership structure. Other investigated determinants, such as industry and country of origin of the issuer, are not found as being relevant.